Penggunaan Multi Process Welding Machine Untuk Menunjang Kegiatan Praktikum Pengelasan Pada Laboratorium Pengelasan Kapal (Welding School) Sekolah Vokasi - Indro Dwi Cahyo (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
The existence of a laboratory is very necessary to fulfill curriculum a chievements. Because laboratory is a mandatory facility to hold any practical classes. Undip Vocational School of Marine Construction Engineering Technology Study Program is using the 2020th